PERANCANGAN TATA RUANG KANTOR DIVISI DR PLANT - Ilham Bashirudin (Teknoin, 2016)
Design work place in accordance with the organization's business processes will encourage efficiency and effectiveness of the functioning of the organization in order to achieve organizational goals. The following journal discussed the design of the layout of the office (office layout) based on business processes and organization. Structuring lay out in the building PTKS DR Plant is also concerned with the health minister of the republic Indonesia Decision No. 1405 / MENKES / SK / XI / 2002 concerning the health requirements of the work environment of offices and industry as well as the Company's internal regulations. The method used is Activity relatioship chart (ARC) ARC is based on business process organsiasi when relations between units in detail can be obtained from the job description, after a calculated area of the room with the organization of the Division of DR Plant obtained that from the extensive building area of 3,297 m2 utilized measuring 2,478 m2 and there is still a vast area of 819 m2 which can be utilized by other units in need.